2022
DOI: 10.1096/fba.2022-00082
|View full text |Cite
|
Sign up to set email alerts
|

FtsZ phosphorylation brings about growth arrest upon DNA damage in Deinococcus radiodurans

Abstract: The polymerization/depolymerization dynamics of FtsZ play a pivotal role in cell division in the majority of the bacteria. Deinococcus radiodurans, a radiationresistant bacterium, shows an arrest of growth in response to DNA damage with no change in the level of FtsZ. This bacterium does not deploy LexA/RecA type of DNA damage response and cell cycle regulation, and its genome does not encode SulA homologues of Escherichia coli, which attenuate FtsZ functions in response to DNA damage in other bacteria. A radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Nevertheless, a DNA damage-responsive Ser/Thr quinoprotein kinase (RqkA) phosphorylates both DNA repair and cell division proteins in this bacterium ( 29 , 39 ). Interestingly, phosphorylation of DNA repair proteins enhances their activity while negatively affecting the functions of the cell division proteins, such as FtsZ, in vitro ( 40 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a DNA damage-responsive Ser/Thr quinoprotein kinase (RqkA) phosphorylates both DNA repair and cell division proteins in this bacterium ( 29 , 39 ). Interestingly, phosphorylation of DNA repair proteins enhances their activity while negatively affecting the functions of the cell division proteins, such as FtsZ, in vitro ( 40 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FtsZ phosphorylation has also affected the functional interaction of FtsZ with FtsA as well as the polymerization dynamics of FtsZ in vitro . Cells expressing phosphor-mimetic mutants of FtsZ behaved differently than cells expressing phosphor-ablative and wild type, indicating the arrest of FtsZ function upon phosphorylation by RqkA ( Chaudhary et al, 2023a ). Furthermore, DivIVA phosphorylation at the T19 site had altered its typical pattern of localization near the new septum site and completely distorted its ability to determine the plane of the next division that is normally perpendicular to the previous plane of cell division ( Chaudhary et al, 2023b ) The enhancement of DNA repair function with the concurrent arrest of cell division upon Ser/Thr phosphorylation by RqkA nearly mimics these processes upon DNA damage as observed in eukaryotes ( Sancar et al, 2004 ).…”
Section: Deinococcus Radiodurans Encodes Putative Substrate ...mentioning
confidence: 99%
“…Deinococcus have also been reported to stop cell division in response to radiation stress; however, the exact mechanism of cell division arrest is not yet fully understood. Recent studies suggested that the phosphorylation of key cell division proteins such as FtsZ or DivIVA by the Serine/Threonine protein kinases (STPKs) (e.g., RqkA) could result in cell cycle arrest under radiation stress in D. radiodurans ( Chaudhary et al, 2023a ; Chaudhary et al, 2023b ). Importantly, both the Deinococcus strain (Ant6 and R1) contains large number of STPK but these proteins were not detected in the radioresistance strain K12 ( Supplementary Table S7 ).…”
Section: Interpretation Of Data Setmentioning
confidence: 99%